Renovation of the Forgotten Ruins and Urban Public Spaces in Sapa Town, Vietnam for Sustainable Development - Lan, Vu Thi Huong; Tran, Quoc Bao (International Journal of Sustainable Construction Engineering and Technology, 2022)
Sapa is one of the famous French towns for tourism in Vietnam with lots of colonial architecture, buildings and urban public spaces which are known for their great historical, cultural, aesthetic, and landscape significance. After the wars in Vietnam, the remaining architectures and public spaces, which were of significant value in terms of history, culture, aesthetics and landscape during the French colonial period in the town, have been severely degraded or arbitrarily renovated. In order to propose solutions for maintaining and promoting the ruined structures and urban public spaces of the town, this study adapted three different sets of criteria for assessment for the urban public spaces, heritage buildings and new buildings. The surveyed urban public spaces and buildings have been ranked in different classes based on their earned total average points in terms of level of usability and value. Proposed strategies adopted were developed based on lessons learnt from previous studies, which include new construction, integration, reservation and relic maintenance